Metabolic reprogramming in glioblastoma: a rare case of recurrence to scalp metastasis - Amir Barzegar Behrooz; Hamid Latifi-Navid; Narges Zolfaghari; Somayeh Piroozmand; Ahmad Pour-Rashidi; Mahsa Bourbour; Fatemeh Jusheghani; Mahmoud Aghaei; Negar Azarpira; Fatemeh Mollasalehi; Sedigheh Alamdar; Ahmad Nasimian; et al. (BJC Reports)
Abstract Background Glioblastoma (GB), an aggressive brain malignancy with a poor prognosis of 1.5–2 years, rarely exhibits extracranial metastasis (ECM). However, metabolic reprogramming has emerged as a key driver of GB progression and invasiveness. This study presents a rare case of recurrent GB with scalp metastasis, exploring how metabolic shifts enable GB cells to evade treatment and adapt to hostile environments, offering insights for developing innovative therapies. Methods Tandem mass spectrometry (MS/MS) was employed to analyze amino acid profiles in both the recurrent and metastatic stages of GB. Systems biology approaches were used to uncover genetic alterations and metabolic reprogramming associated with the progression from recurrence to metastasis. Results Our analysis revealed distinct amino acid utilization patterns in a patient with a molecular phenotype of wild-type IDH-1&2, TERT mutation, non-mutated BRAF and EGFR, and non-methylated MGMT. During recurrence and metastasis, significant differences in amino acid profiles were observed between blood and cerebrospinal fluid (CSF) samples. Additionally, protein-protein interaction (PPI) analysis identified key genomic drivers potentially responsible for the transition from recurrent to metastatic GB. Conclusions Beyond established risk factors such as craniotomy, biopsies, ventricular shunting, and radiation therapy, our findings suggest that metabolic reprogramming plays a crucial role in the transition from recurrent to metastatic GB. Targeting these metabolic shifts could provide new avenues for managing and preventing extracranial metastasis in GB, making this an important focus for future research.